Extending the frontiers of knowledge: the report of a Royal College of Physicians-sponsored study visit - Akanbi, Maxwell O (Clin Med (Lond), 2009)
This is a report of a Royal College of Physicians-sponsored study visit to the UK. The ‘Taking knowledge overseas’ scheme enables promising, talented and motivated physicians to have access to high-quality postgraduate educational experience early in their career which will stimulate learning and encourage them to share good practice and knowledge on their return home. By the end of 2008, 26 doctors from low-income countries had benefited from the programme.